Does Computer-Assisted Instruction (CAI) Influence Academic Performance of High School Students in Social Studies? Evidence from the Philippines - Kenneth P. Panga; Julius Jared N. Canale; Emmanuel Onsay (MASI Mandiri Edukasi, 2025)
The study investigates the impact of computer-assisted instruction (CAI) on Grade 9 students' academic performance and attitudes towards learning Araling Panlipunan (Social Studies) at San Jose National School and Goa National School in the Philippines. Using a descriptive correlational design, it explores the relationships between the perceived effectiveness of CAI, attitudes towards its use, and academic performance. Students at both schools view CAI positively, recognising its benefits in enhancing assessment performance, critical thinking skills, and information retention. While they appreciate the supplementary materials, traditional teaching methods are slightly favoured for overall effectiveness and real-world application of knowledge. A low positive correlation exists between academic performance and perceived effectiveness at San Jose National School, implying that a better perception of CAI effectiveness may boost academic performance. Conversely, at Goa National School, a moderate positive correlation exists between academic performance and perceived effectiveness and attitude towards CAI, suggesting that a positive view and effectiveness of CAI correspond to improved academic outcomes. Enhancing students' perceptions of CAI could improve academic performance, highlighting the need for continued refinement of CAI strategies for enhanced learning experiences in Araling Panlipunan.